Inflation uncertainty revisited: A proposal for robust measurement - Christian Grimme; Steffen Henzel; Elisabeth Wieland (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
Any measure of unobserved inflation uncertainty relies on specific assumptions which are most likely not fulfilled completely. This calls into question whether an individual measure delivers a reliable signal. To reduce idiosyncratic measurement error, we propose using common information contained in different measures derived from survey data, a variety of forecast models, and volatility models. We show that all measures are driven by a common component which constitutes an indicator for inflation uncertainty. Moreover, the idiosyncratic component of survey disagreement contains systematic measurement error during economic downturns. Finally, we study the Friedman-Ball hypothesis. Using the indicator, it turns out that higher inflation is followed by higher uncertainty. By contrast, we obtain contradictory results for the individual measures. We also document that, after an inflationary shock, uncertainty decreases in the first two months which is traceable to the energy component in CPI inflation.
Keywords: C53; E31; E37; 330; Inflation uncertainty; inflation; survey data; stochastic volatility; GARCH; principal component analysis; Inflation; Risiko; Volatilität; Messung; Inflationsrate; ARCH-Modell; Schätzung; USA